Analysis of the Impact of Landslides and Floods on Train Travel Graph Operation Patterns and Signaling Systems on the Mandai-Garongkong Line - Muhadzdzib, Nazul; Hakim, Mohamad Lukman; Nugraha, Nathanael Tegar Putra; Darmawan, Arief (Siber Journal of Advanced Multidisciplinary, 2025)
Floods and landslides are natural disasters that have a major impact on transportation modes, especially in the land transportation sector. As a result of the disaster, many land travel routes were hampered and in the case of the railway sector, it had a very significant impact. The existence of floods and landslides resulted in the train operating system not running properly. This study aims to analyze the impact of floods and landslides on Train Travel Graph operating patterns and the effect on the railway signaling system by using the scoring method to obtain the results of mapping the level of flood and landslide risk and qualitative methods by analyzing documents and interviewing resource persons in order to obtain accurate information related to the cases that occur at each station. In this study, focusing on the province of South Sulawesi, in the Makassar Pare Pare railway project, there are several flood and landslide events that have occurred and the most significant impact on the Train Travel Graph operation pattern and signaling system are in the case of floods at Maros station and landslides at KM 72 in the Mandalle and Tanete Rilau station areas. The incident resulted in the cessation of train operations and the disconnection of the railway operation line which was supposed to be the Mandai Garongkong line but was cut off and ended at Mandal station. This incident can finally be handled by turning off all component functions in the railway interlocking system in flood handling. By using gutters and gabions in the KM 72 area to minimize the occurrence of further landslides and the crossing method carried out on Fiber Optic cables to keep the cable away from the risk of landslides.